Features of Orthodox Ecumenism - Oleh S. Kyselov (Українське Pелігієзнавство, 2006)
One of the main characteristics of the history of Christianity of the twentieth century. one can confidently call the attraction of different churches and denominations to convergence within the ecumenical movement. The purpose of this movement is Christian (church) unity, but despite some success, it has not been achieved. Not only the difference in Christian dogma and vision of spiritual life, but also the conceptual understanding of unity played a role here.